Regional mix and the roles of foreign subsidiaries: A new conceptualization and empirical evidence on the UK case - Constantina Kottaridi; Fragkiskos Filippaios; Marina Papanastassiou; Robert Pearce (SPOUDAI - Journal of Economics and Business, 2013)
This paper develops a new conceptualization of the relationship between regional determinants and roles of foreign subsidiaries and empirically investigates this relationship in the UK at a disaggregated regional level. It focuses particularly on a relatively under- investigated field, that of the linkage between choice of regional location -within a particular host country- and subsidiary roles. The key contribution steaming from this analysis is the development of the Asset Specificity Framework (ASF) combining regional characteristics with distinctive types of subsidiaries. This framework is further examined providing detailed support for our allegations. The external environment impacts differently on subsidiary types, with agglomeration features playing the most significant role. At the same time though, idiosyncratic Foreign Direct Investment (FDI) aspects do seem to exert the most important influence for these types of subsidiaries. Interesting policy implications may then be raised regarding the design of well-targeted FDI promoting policies, aiming at upgrading regional potential on one hand and pursue the attraction of specific sectors and companies on the other.
Keywords: F23; L20; R10; 330; UK Regions; subsidiaries' roles; regional mix; location choice; agglomeration